2009
DOI: 10.1653/024.092.0316
|View full text |Cite
|
Sign up to set email alerts
|

Egg Paeasitoids ofDalbulus maidis(Hemiptera: Cicadellidae) in Jalisco State, Mexico

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Dalbulus maidis feeds and reproduces on maize (Nault 1990), where females insert eggs into the plant tissue, with most eggs being laid in clusters on the midrib of the leaf (Heady et al 1985). In Mexico, eggs of D. maidis on maize are parasitized by Anagrus breviphragma Soyka (Hymenoptera: Mymaridae), which was recently synonymized under A. incarnatus Haliday (Triapitsyn 2015), A. columbi Perkins, and Polynema saga (Girault) (all Hymenoptera: Mymaridae), and also by Aphelinoidea semifuscipennis Girault, Oligosita clarimaculosa (Girault), Oligosita desantisi Viggiani, Oligosita sp., Paracentrobia tapajosae Viggiani, and Pseudoligosita longifrangiata (Viggiani) (all Hymenoptera: Trichogrammatidae) (Virla et al 2009;Moya-Raygoza et al 2012Moya-Raygoza & Becerra-Chiron 2014); however, identification of the two last species needs verification. Mexico is considered to be the center of origin of the genus Dalbulus DeLong (Nault 1990).…”
mentioning
confidence: 99%
“…Dalbulus maidis feeds and reproduces on maize (Nault 1990), where females insert eggs into the plant tissue, with most eggs being laid in clusters on the midrib of the leaf (Heady et al 1985). In Mexico, eggs of D. maidis on maize are parasitized by Anagrus breviphragma Soyka (Hymenoptera: Mymaridae), which was recently synonymized under A. incarnatus Haliday (Triapitsyn 2015), A. columbi Perkins, and Polynema saga (Girault) (all Hymenoptera: Mymaridae), and also by Aphelinoidea semifuscipennis Girault, Oligosita clarimaculosa (Girault), Oligosita desantisi Viggiani, Oligosita sp., Paracentrobia tapajosae Viggiani, and Pseudoligosita longifrangiata (Viggiani) (all Hymenoptera: Trichogrammatidae) (Virla et al 2009;Moya-Raygoza et al 2012Moya-Raygoza & Becerra-Chiron 2014); however, identification of the two last species needs verification. Mexico is considered to be the center of origin of the genus Dalbulus DeLong (Nault 1990).…”
mentioning
confidence: 99%
“…This is the first report of O. desantisi attacking D. maidis eggs in Mexico. In previous studies in the same sites the following parasitoids were found attacking D. maidis eggs: A. breviphragma, A. semifuscipennis, Oligosita clarimaculosa (Girault), P. tapajosae, Polynema saga (Girault), and P. longifrangiata in El Grullo and A. breviphragma, A. semifuscipennis, O. clarimaculosa, and P. tapajosae in Zapopan (Virla et al 2009;Moya-Raygoza et al 2012). This is the first report of parasitoids attacking D. elimatus eggs.…”
Section: Egg Parasitoids Of the Leafhoppers Dalbulus Maidismentioning
confidence: 78%
“…Previous surveys identified 6 egg parasitoid species of D. maidis in Jalisco, Mexico (Virla et al 2009;Moya-Raygoza et al 2012). However, no reports of D. elimatus egg parasitoids are available.…”
Section: Egg Parasitoids Of the Leafhoppers Dalbulus Maidismentioning
confidence: 99%
“…Specimen collection. Essentially the same method was used to rear parasitoids of D. maidis in Argentina and Mexico, using sentinel eggs exposed in the cornfields free of pesticide applications during corn growing season (Virla et al 2009. To obtain sentinel eggs, 6-10 females of D. maidis were placed in cages (35 cm high × 18 cm diameter) on leaves of potted maize plants in their vegetative stage for oviposition.…”
Section: Methodsmentioning
confidence: 99%